2009
DOI: 10.1519/jsc.0b013e3181910746
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Duration of Resistance Training Interventions in Children Who Are Overweight or Obese

Abstract: The purpose of this study was to investigate the effects of different durations of resistance training on body composition and power in children. The study was a 24-week longitudinal design involving 31 preadolescent children who were overweight or obese (ages 7-12 years), divided into 3 groups and resistance trained 3 times per week. Group 8 (G8) trained for 8 weeks, group 16 (G16) trained for 16 weeks, and group 24 (G24) trained for 24 weeks. All participants were measured at weeks 0, 8, 16, and 24 for body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 12 publications
3
32
0
4
Order By: Relevance
“…Obesity develops as triglyceride deposits increase in adipose tissue, with a consequential decrease in the insulin response in muscle and adipose tissue. 12,17 Resistance to insulin is undoubtedly one of the most significant mechanisms causing complications of obesity. 12 The present study showed that positive changes were observed in body weight, body composition and blood lipid levels in children aged 10 -12 years after 12 weeks of regular exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity develops as triglyceride deposits increase in adipose tissue, with a consequential decrease in the insulin response in muscle and adipose tissue. 12,17 Resistance to insulin is undoubtedly one of the most significant mechanisms causing complications of obesity. 12 The present study showed that positive changes were observed in body weight, body composition and blood lipid levels in children aged 10 -12 years after 12 weeks of regular exercise.…”
Section: Discussionmentioning
confidence: 99%
“…16 Weight gain in childhood, even at moderate levels, tends to continue into adulthood and can cause serious problems. 17 The duration of obesity is an independent indicator for the effects of obesity on health. 16 The development of persistent obesity is more likely when weight gain occurs in early childhood, during the pre-pubertal development period or during adolescence.…”
Section: K Karacabey Exercise Effect On Leptin Insulin Cortisol Andmentioning
confidence: 99%
“…Regular participation in youth resistance training programme has been shown to elicit favourable short-term influences on musculoskeletal health, body composition and cardiovascular risk factors 11 74 – 77. However, following a period of detraining (8–12 weeks) various measures of muscular fitness appear to regress towards baseline values,7880 suggesting that engagement in resistance training should be viewed as a long-term, year-round commitment to a well-constructed and varied periodised programme.…”
Section: Health Benefits Of Resistance Training For Youthmentioning
confidence: 99%
“…Such progression should provide the child with sufficient exposure in order to aid motor control development, while serving as a suitable volume for physical conditioning. As training age and athletic competency increases, youth can be introduced to periodic phases of lower repetition ranges (≤6) and higher external loads (>85% 1 RM) in training, on the proviso that technical competency remains 15 77 200 234 235…”
Section: Resistance Training Guidelines For Children and Adolescentsmentioning
confidence: 99%
“…[13][14][15][16]18,[20][21][22][23][24][25][26][27][28] Although these studies individually analyzed small numbers of patients, they collectively assessed . 300 age-matched children and adolescents.…”
Section: Future Researchmentioning
confidence: 99%